The Concept of Tanasuh - Azranee Bin Abdullah (Universiti Sains Islam Malaysia, 2009)
During this study, the author mainly used data collection methods, in which contains data analyzing verses from Holy Qur'an and authentic Sunnah, local academic books and other references from overseas. The aim of this study is to perform the true concept of advices, and reasons of how important it is to be implemented by Muslims nowadays. Thus, by revealing the true concept of advices, Muslims may keep reprimanding each others as it will erect the exclamation of Islam itself.